Risk, demand, capacity and outcomes in adult specialist eating disorder services in South-East of England before and since COVID-19. (April 2022) - Ayton, Agnes; Viljoen, David; Ryan, Sharon; Ibrahim, Ali; Ford, Duncan
Abstract : Aims and method: This is a longitudinal cohort study describing the demand, capacity and outcomes of adult specialist eating disorder in-patient services covering a population of 3.5 million in a South-East England provider collaborative before and since the COVID-19 pandemic, between July 2018 and March 2021. Results: There were 351 referrals for admission; 97% were female, 95% had a diagnosis of anorexia nervosa and 19% had a body mass index (BMI) <13. Referrals have increased by 21% since the start of pandemic, coinciding with reduced capacity. Waiting times have increased from 33 to 46 days. There were significant differences in outcomes between providers. A novel, integrated enhanced cognitive behaviour theapy treatment model showed a 25% reduction in length of stay and improved BMI on discharge (50% v. 16% BMI >19), compared with traditional eclectic in-patient treatment. Clinical implications: Integrated enhanced cognitive behaviour theapy reduced length of stay and improved outcomes, and can offer more effective use of healthcare resources.